The Influence of Company Image on Consumer Purchase Decisions at Alfamart Jatiwaringin Bekasi Branch - Ardani, Wayan (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
This study aims to determine the effect of corporate image on purchasing decisions at Alfamart Branch Jatiwaringin Bekasi. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study on the company image variable obtained an average score of 3.41 with good criteria. Purchasing decision variable obtained an average score of 3.84 with good criteria. Corporate image has a significant effect on purchasing decisions with the regression equation Y = 9.626 + 0.845X, and a correlation value of 0.785 or strong with a determination of 61.6%. The hypothesis test obtained a significance of 0.000 <0.05.